CHARACTERIZATION OF SUPERNATANT EXTRACT AND VIABILITY OF BACILLUS SUBTILIS KM16 AND PSEUDOMONAS SPP. IN FISH FEED AS BIOCONTROL AGENTS AGAINST AQUACULTURE PATHOGENS - Stella Magdalena; Brenda Kristanti; Yogiara Yogiara (Research Center for Biology-Indonesian Institute of Sciences, 2021)
The use of biocontrol agent in aquaculture is being adapted as an effective alternative to antibiotics which can lead to the elaboration of antibiotic-resistant bacteria and confer unpleasant impacts to aquatic organisms. Aquatic bacteria have been discovered as biocontrol agents and potential probiotic candidates to improve the health of aquatic organisms, feed efficiency, and disease resistance to aquaculture pathogens. However, local isolate has not intensively been explored and used to increase aquaculture sector productivity. Therefore, this research aimed to determine minimum inhibitory concentrations of their antibacterial compounds against aquaculture pathogens and to characterize aquatic bacteria by their viability in the feed. Four isolates from several aquatic environments in Indonesia (Pseudomonas sp. S1.1, Pseudomonas sp. S1.2, Pseudomonas sp. SL1.1, and Bacillus subtilis KM16) were used to characterize of antibacterial compound and to determine the viability in feed. Ethyl acetate extracts from all isolates showed better antibacaterial activity against Aeromonas hydrophila and Vibrio vulnificus than chloroform and dichloromethane extracts, in which ethyl acetate extract from Bacillus subtilis KM16 showed the strongest antibacterial activity. Pseudomonas spp. were more effective against V. vulnificus (40 mg/mL) and Bacillus subtilis KM16 was more effective against A. hydrophila (20 mg/mL), as proved by the minimum inhibitory concentrations of their ethyl acetate extracts. In this research, Bacillus subtilis KM16 had stable viability in feed than Pseudomonas sp. isolates.